Dysfunctional Family and Toxic Parenting Style in the Autobiographical Novel The Kid - Wibowo, Raden Nur Prasetyo; Syamsudin, Oom Rohmah (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2023)
Abstract. This study describes a theme of dysfunctional family, toxic parenting style, and main character’sdevelopment in The Kid novel by investigating the representation of dysfunctional family and toxic parenting style. This study also reveals how the protagonist copes with the problems caused by dysfunctional family and toxic parenting style in terms of character development. The research applies semiotic analysis of Saussure and structural approach (Todorov, 1985) requiring the study to focus on syntax, semantic and verbal aspect. As a result, the novel represents dysfunctional family in the way that it is chaotic based on Hunt's perpsective (2014) and toxic parenting style (Buck & Forward, 2002). Moreover, the main character Kevin Lewis deals with the toxic parents and develops as a child to adult character. The parents hurt the child in the way that they are toxic instead of caring with proper nurture. The toxic parents are inadequate to support the family, controlling towards Kevin, physically and verbally abusive. Kevin Lewis has some psychological issues as the effect of having toxic parents; struggling, anxious, stress, traumatic, low self-esteem, unhappy, bulimic and suicidal. He wants to be better, and he struggles to change. He can cope with the issues in the way that he is thoughtful, finance-oriented, sympathetic and empathetic. Moreover, he is able to deal with his bulimia well. At the end, he is a happy and functional parent.Keywords: character development; dysfunctional family; semiotic analysis; structural approach; toxic parentingAbstrak. Penelitian ini mendeskripsikan tema keluarga disfungsional, pola asuh orang tua yang kurang baik, dan perkembangan tokoh utama dalam novel The Kid dengan menyelidiki representasi keluarga disfungsional dan pola orang tua asuh yang kurang baik. Penelitian ini juga mengungkapkan bagaimana tokoh utama mengatasi masalah yang disebabkan oleh disfungsi keluarga dan pola orang tua asuh yang kurang baik dalam hal perkembangan karakter. Penelitian ini menggunakan analisis semiotik Saussure dan pendekatan structural (Todorov, 1985) pada aspek sintaksis, semantik, dan verbal. Penelitian ini menyelidiki lingkungan rumah tangga dari keluarga disfungsional yang kacau berdasarkan teori dari Hunt (2014), pola asuh yang kurang baik (Buck & Forward, 2002), bagaimana karakter utama Kevin Lewis menghadapi orang tua dengan pola asuh sedemikian rupa dan tokoh utama berkembang hingga dewasa. Orang tuanya menyakiti Kevin Lewis dengan pola asuh yang kurang tepat tepat. Orang tuanya dengan pola asuh seperti kurang mampu menghidupi keluarga, terlalu mengendalikan Kevin, kasar secara fisik dan verbal. Kevin Lewis memiliki beberapa masalah psikologis akibat memiliki orang tua dengan pola asuh tersebut; ia bersusah payah, cemas, stres, traumatis, harga diri yang rendah, tidak bahagia, bulimia dan ingin bunuh diri. Dia ingin menjadi lebih baik, dan dia berjuang untuk berubah. Dia dapat mengatasi permasalahan dengan menjadi bijaksana, berorientasi keuangan, simpatik dan empati. Apalagi ia mampu mengatasi bulimia yang dideritanya dengan baik. Pada akhirnya, dia juga bahagia dan menjadi orang tua yang fungsional.Kata kunci: analisis semiotik; disfungsi keluarga; pendekatan struktural; pola asuh yang kurang baik, perkembangan karakter